2009
DOI: 10.1111/j.1751-0813.2008.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the non‐steroidal anti‐inflammatory drug, carprofen, on weaned sheep following non‐surgical mulesing by intradermal injection of cetrimide

Abstract: In weaner sheep, carprofen ameliorated the behavioural responses, but was unable to provide relief from the intense and sustained physiological responses to non-surgical mulesing by intradermal injection of cetrimide. Systemic side-effects may be unavoidable with formulations based on quaternary ammonium compounds that are designed to reduce the risk of fly strike in sheep by remodelling breech tissue through induction of tissue necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 16 publications
7
28
0
Order By: Relevance
“…The main findings of this study are that intradermal injection of SLS caused an inflammatory reaction around the breech and tail, resulting in systemic sequelae of fever, increased cortisol and haptoglobin concentrations, and moderate changes in normal behavioural postures. Gross tissue reactions of swelling and scab formation were mild in comparison to the reported response to intradermal injection of cetrimide 6–8 . Skin sites treated with SLS were mildly swollen for several days, then became indurated.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The main findings of this study are that intradermal injection of SLS caused an inflammatory reaction around the breech and tail, resulting in systemic sequelae of fever, increased cortisol and haptoglobin concentrations, and moderate changes in normal behavioural postures. Gross tissue reactions of swelling and scab formation were mild in comparison to the reported response to intradermal injection of cetrimide 6–8 . Skin sites treated with SLS were mildly swollen for several days, then became indurated.…”
Section: Discussionmentioning
confidence: 82%
“…From that work, cetrimide was chosen for further research and development. Recent assessments of the response to intradermal injection of a modified formulation based on cetrimide into the breech and tail of lambs found physiological responses of a similar magnitude to mulesing, but behavioural responses generally of lesser magnitude than those seen in mulesed lambs 6–8 . These results suggested that further modifications to the delivery method or formulation may be needed to lessen the undesirable effects.…”
mentioning
confidence: 99%
“…Wound healing was slower after intra-dermal centrimide in comparison with mulesing 63 with reports of severe bruising, 109 and marked initial swelling before subsequent formation of hard scabs with observed substantial purulent exudate beneath lifted scabs. 108 Wound bed contraction was similar in mulesed and centrimide treated sheep.…”
Section: Delivery Of Accurate Drug Dose Into the Tissuementioning
confidence: 88%
“…Needleless intra-dermal injection of 4% cetrimide (alkyltrimethylammonium bromide, a quaternary ammonium compound) into lambs 104 and sheep 108 with and without pre-treatment of carprofen (long acting non-steroidal anti-inflammatory drug) resulted in physiological increases in cortisol and haptoglobin. However sheep pre-treated with carprofen displayed less abnormal postures of discomfort than the other groups.…”
Section: Delivery Of Accurate Drug Dose Into the Tissuementioning
confidence: 99%
See 1 more Smart Citation